Aturan Penetapan Status Tersangka Gratifikasi Kepada Pejabat Pemerintah yang Belum Diperiksa oleh KPK Menurut Undang-Undang Tindak Pidana Korupsi - Yeni Sandy Bangun, Yeni Sandy Bangun; Marlina; Detania Sukarja (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
The determination of suspect status for alleged gratification to government officials who have not been examined by the KPK should be based on sufficient evidence and a fair legal process. Based on the description, the problems in this study are: How to identify gratification of government officials who have not been examined by the KPK according to criminal procedure law, how to apply the law on determining suspect status for gratification to government officials who have not been examined by the KPK in Indonesia, and what legal efforts are made by suspects of gratification status to government officials who have not been examined by the KPK. Identification of gratification of government officials who have not been examined by the KPK according to criminal procedure law should be guided by the mechanism for fulfilling valid evidence based on Article 184 of the Criminal Procedure Code. Regarding the determination of suspects, it is regulated based on the Criminal Procedure Code which has then been refined with the Decision of the Constitutional Court (MK) Number 21/PUU-XII/2014 dated April 28, 2015, in the decision it is explained that the determination of suspects must be based on at least 2 (two) pieces of evidence as contained in Article 184 of the Criminal Procedure Code and accompanied by the examination of the suspect candidate.